2015
DOI: 10.1097/inf.0000000000000719
|View full text |Cite
|
Sign up to set email alerts
|

Australia-wide Point Prevalence Survey of Antimicrobial Prescribing in Neonatal Units

Abstract: This is the first Australia-wide point prevalence survey of neonatal antimicrobial prescribing in tertiary children's hospitals. The findings highlight positive practices and potential targets for quality improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 33 publications
3
38
2
Order By: Relevance
“…Large-scale analysis of antibiotic prescribing and appropriateness for neonatal sepsis has not been reported in Australia. Information on neonatal empiric guideline use 21 and prescribing 22 has been reported from selected large neonatal intensive care units, but this excludes many health services providing neonatal care. Hospitals use a variety of different guidelines for selection and dosing of empiric antibiotic therapy in neonates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large-scale analysis of antibiotic prescribing and appropriateness for neonatal sepsis has not been reported in Australia. Information on neonatal empiric guideline use 21 and prescribing 22 has been reported from selected large neonatal intensive care units, but this excludes many health services providing neonatal care. Hospitals use a variety of different guidelines for selection and dosing of empiric antibiotic therapy in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals use a variety of different guidelines for selection and dosing of empiric antibiotic therapy in neonates. [21][22][23][24] Benzylpenicillin and gentamicin are recommended for empiric treatment of neonatal sepsis in current national guidelines 20 and are appropriate empiric therapy for the majority of organisms responsible for EOS in Australia. 6 This study confirms these are frequently used currently, although with considerable variation in administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A widespread PPS performed in 50 European and 23 non-European hospitals of 23 countries (14 European and 9 non-European countries) revealed a very high use of broad spectrum antibiotics in pediatric and neonatal in-patients from non-European countries as compared to Europe (11). A PPS performed on 6 newborn units in Australia reported that 46% of inpatients were administered at least 1 antibiotic, (16). In another study performed at a level III NICU, on 1607 infants during a period of 14 months, 72% of neonates were given 1 or more courses of antibiotics; these figures are comparable to the current study (17).…”
Section: Discussionmentioning
confidence: 99%
“…Penicillin, gentamicin, and ampicillin were the most frequently used antibiotics for neonates in many studies; vancomycin, however, was not used often and was administered only in 1% of patients in one of the studies. Moreover, meropenem and cefotaxime were among the least-used antibiotics (16,17,20). There is a paucity of randomized controlled trials to approve the most optimal antibiotic regimens for the treatment of neonatal sepsis, yet most experts recommend the empirical use of ampicillin together with an aminoglycoside for EOS and anti-staphylococcal penicillin together with an aminoglycoside for LOS.…”
Section: Discussionmentioning
confidence: 99%